TRANSLINGUALISM ACROSS LANGUAGES: A TEXTUAL ANALYSIS OF LANGUAGES INTERACTION - Malephole Sefotho; Erasmus Charamba; Genevieve Quintero (Education. Innovation. Diversity, 2023)
The myth of a pure form of language is so deep-rooted in many people that, even though they accept the existence of different languages, they cannot accept the reality that there is no language that is fully independent of other languages. People believe that there is language contamination across languages and most of the time it is their own language contaminated by others. This confirms the colonial principle of compartmentalization or distribution of languages. Even in the post-colonial era, language isolation remains a serious challenge, especially in bi/multilingual classroom settings, where learners are discouraged to translanguage or code-mesh languages. It is against this background that this paper examines adaptation of several vocabularies and concepts from other languages in developing a language, usually through merging of cultures or colonization. This study looks at examples in Southern Africa and the Philippines of existing fusion that has taken place between those languages and other surrounding languages. Therefore, this study argues that boundaries between languages are fluid - not fixed. The boundaries do not exist. They are therefore uncalled for because they destabilize the fluidity between languages, yet there is autonomous fusion between languages. We further argue that indigenization of languages can work well in translanguaged classrooms where learners are allowed to utilize indigenized versions of loan words to express ideas and concepts. This can encourage a more liberal use of language and self-expression in formal classroom settings.